Preparation of Betulone Via Betulin Oxidation Over Ru Nanoparticles Deposited on Graphitic Carbon Nitride; Catalysis Letters; Vol. 149, iss. 3 - Shcherban N. D.; Maki-Arvela P.; Aho A.; Sergienko S. A.; Skoryk M. A.; Kolobova E. N. Ekaterina Nikolaevna; Simakova I. L.; Eranen K.; Smeds A.; Hemming J.; Murzin D. Yu. (2019, 2019)
Title screen